Implementation and evaluation of optimal algorithms for computing association rule learning (International Journal of Engineering and Computer Science, 2017)
One of the well-researched and most important techniques of mining data is Association Rule Mining. Association Rules as the name itself indicates includes finding correlations among sets of items in transaction database. The proposed work is based on automobiles study and will help the sellers and customers in making decisions. The objective is to find the important selling factors that affect the relevant sale of vehicles by using the association rule mining algorithm. Most famous algorithm of association rule mining is Apriori is used for knowledge discovery. Research work will improve the existing Apriori algorithm and will reduce some of the drawbacks of the existing algorithm.